Cardiorespiratory/sedative effects of a peptide identified in crotalic venom compared to acepromazine and xylazine in horses - C. J. X. Abimussi; M. D. Eneas; B. P. Floriano; G. Picolo (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2023)
ABSTRACT The purpose of this study was to investigate whether intravenous crotalphine produces significant sedation, as well as physiological changes, in healthy standing horses. Six mares, aged 8 years and weighing 415kg underwent three different treatments in a crossover design: TA (acepromazine: 50μg.kg-1), TC (crotalphine: 0.01μg.kg-1) and TX (xylazine: 1000μg.kg-1), intravenously. At various time points over 60 minutes, physiologic variables were recorded: heart rate, respiratory rate, and rectal temperature. The head height from the ground (HHG) was evaluated in centimeters. Data were analyzed using ANOVA followed by Dunnett’s test or Friedman followed by Dunn’s test, under 5% significance. Heart rate decreased significantly at M5 and M10 compared with Mb in TX (28±7, 26±6 and 40±8 beats/minute-1, respectively; p=0.0004). Respiratory rate and rectal temperature did not differ among groups or time points. The HHG significantly decreased in all groups compared with Mb at various time points (p<0.0001). In conclusion, crotalphine did not produce reliable and durable sedation in healthy standing mares and did not influence cardiorespiratory variables in a clinically relevant manner.